ANALISIS PENERAPAN PENYUSUNAN LAPORAN KEUANGAN DAERAH PEMERINTAH KOTA MAKASSAR BERBASIS AKRUAL SESUAI PERMENDAGRI - mahyudin usman (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2022)
The research aims to analyze the region financial report writing of Makassar government based on the Government Accountancy Standard based accrual appropriated with the Government Regulation Number 71 of the year 2010, in Region Finance and Asset Management Institution. The research method used is qualitative research. Qualitative research in this research means the research that tries to express the problem solving through the data obtained from the informants and literature sources such as the Major Regulation of Makassar and the Government Regulation Number 71 of the year 2010 about accrual accountancy based and other literature sources that were relevant with this research. Based on the research findings, the financial report writing of the Region Government of Makassar City through the Finance and Asset Management Institution showed that on the transaction record, admission, measurement, and the statement related to the transaction records: (a) Income Accountancy; (b) Expenditure and Load Accountancy; (c) Asset Accountancy; (d) Obligation Accountancy; and (e) Finance Accountancy have fulfilled the accrual standard for the government accountancy system. And for the finance report, the Region Government of Makassar City has provided finance report elements based on PP 71 of the year 2010 that the finance report has the following elements: (a) Budgeting Realization Report; (b) Over Budget Balance Change Report; (c) Balance Sheet; (d) Operational Report; (e) Cash Flow Report; (f) Equity Change Report; and (g) Notes on the Financial Report.